Pathogenesis of Opsoclonus Myoclonus - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
The proceedings of the 2nd International Opsoclonus Myoclonus Ataxia Syndrome (OMAS) Symposium (Feb 6-8, 2003; Abingdon, Oxfordshire, UK) are summarized from the Neurosciences Unit, Institute of Child Health, University College, London, UK.